Hubungan Pengetahuan dengan Stigma Masyarakat Terhadap Penderita Penyakit Kusta di Desa Karyamukti Wilayah Kerja Puskesmas Sekampung Kabupaten Lampung Timur - Trismiyana, Eka; Triyoso, Triyoso; Hidayat, Taufiq (Universitas Malahayati, 2024)
ABSTRACT Leprosy is an infectious disease caused by a bacterium. It affects the peripheral nerves, skin, mucous membranes (mouth), upper respiratory tract, reticuloendothelial system, eyes, muscles, bones, and testes. There are two types of leprosy, namely wet type MB (Multi Bacillary) and dry type PB (Pasui Bacillary). This disease remains problematic in Indonesia with 403 new cases reported in 2021. While in Lampung Province, there were 122 patients with a prevalence rate of 0.20 per 10,000 population in 2021. Especially in East Lampung Regency, there were 14 new cases reported in 2021, with a prevalence rate of 0.2 per 10,000 population. This study was to determine the relationship between knowledge and community stigma towards leprosy patients in Karya Mukti Village, working area of Sekampung Primary Health Center, East Lampung Regency in 2023. This study used a quantitative approach with an analytical survey design using a cross-sectional approach. The population of this study included all residents in Karya Mukti Village, totaling 1,200 families. The sample size of 300 families determined using random sampling technique. The data were analysed using the Chi-Square statistical test. Based on the frequency data, 40 (13.3%) respondents had good knowledge about leprosy, while 260 (86.7%) respondents had poor knowledge. Regarding the frequency of community stigma towards leprosy patients, 138 (46.0%) showed positive stigma, and 162 (54.0%) showed negative stigma. The Chi-Square test resulted in a p-value of 0.001 (<0.05) with an Odd Ratio of 3.182. There is a relationship between knowledge and community stigma towards leprosy patients (p-value 0.001, OR 3.182) in Karya Mukti Village, working area of Sekampung Primary Health Center of East Lampung Regency in 2023. It is recommended for the primary health center to enhance community activities by providing health education to improve awareness among the community about leprosy, particularly regarding the transmission process. By understanding how leprosy is transmitted, the community can overcome negative perceptions and fear associated with the disease, which has long been considered dangerous. Keywords: Knowledge, Stigmatization, and Leprosy ABSTRAK Kusta merupakan jenis penyakit menular melalui kuman, Penyakit ini menyerang syaraf tepi, kulit, mukosa (mulut), saluran pernapasan bagian atas, sistem retikulo endotelia, mata, otot, tulang, dan testis. dan ada 2 jenis penyakit kusta yaitu kusta basah tipe MB (Multi Bacillary), kusta kering tipe PB (Pasui Bacillary) yang masih menjadi permasalahan di Indonesia sebanyak 4,03 kasus baru pada th 2021 dan diprovinsi lampung sebanyak 122 penderita dengan angka prevelensi 0,20 per 10.000 penduduk tahun 2021 khususnya di Kabupaten Lampung Timur Pada tahun 2021 terdapat penemuan kasus baru yang menderita penyakit kusta sebanyak 14 penderita dengan angka prevelensi 0,2 per 10.000 penduduk. Diketahui Hubungan Pengetahuan Dengan Stigma Masyarakat Terhadap Penderita Kusta Di Desa Karya Mukti Wilayah Kerja Puskesmas Sekampung Kabupaten Lampung Timur Tahun 2023. Jenis penelitian kuantitatif. Rancangan survey analitik dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah semua masyarakat yang ada di Desa Karyamukti sebanyak 1200 Kepala Keluarga (KK) deangan jumlah sempel 300 Kepala Keluarga (KK). Pengambilan sampel menggunakan teknik random sampling. Analysis data menggunakan uji statistik Chi Square. Berdasarkan data frekuensi pengetahuan tentang penyakit kusta berpengetahuan baik 40 (13.3%), berpengetahuan kurang 260 (86.7%) dan data frekuensi stigma masyarakat terhadap penderita penyakit kusta stigma positif 138 (46.0%), stigma negatif 162 (54.0%). Hasil uji Chi-square didapatkan nilai p value 0.001 (<0.05) dengan Odd Ratio 3.182. Adanya hubungan pengetahuan dengan stigma masyarakat terhadap penderita penyakit kusta (p value 0.001. OR 3.182) di Desa Karyamukti Wilayah Kerja Puskesmas Sekampung Lampung Timur tahun 2023. Bagi pihak Puskesmas disarankan meningkatkan kegiatan bagi masyarakat dengan cara memberikan pendidikan kesehatan kepada masyarakat tentang penyakit kusta khususnya proses penularan penyakit kusta. Sehingga dengan mengetahui penularan penyakit kusta, masyarakat tidak lagi memiliki anggapan negatif dan takut dengan penyakit kusta yang selama ini dianggap sebagai penyakit yang berbahaya. Kata Kunci: Pengetahuan, Stigmatisasi, dan Kusta